2022
DOI: 10.1021/acs.jchemed.1c00632
|View full text |Cite
|
Sign up to set email alerts
|

Not All Chemists are White Men: Incorporating Diversity in the General Chemistry Curriculum

Abstract: We have developed and implemented a change to our General Chemistry curriculum that makes the point that not all chemists are white men. This builds on recent textbook analyses, which showed that General Chemistry textbooks overwhelmingly and unnecessarily focus on the biographies of scientists that are white men. We demonstrate a way to highlight contributions from female chemists and chemists of color to illustrate General Chemistry concepts. We describe how this work could be extended and used in tandem wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Reis and Mensinger have reported that biographical information of diverse scientists should connect to the taught content rather than act as stand-alone elements, 4 whilst Gee et al suggest the use of "Try this" problems to connect with lecture material. 30 A study of student views on decolonization suggests that who is teaching the curriculum, and how it is delivered (e.g., through the use of active learning) are also important considerations. 37 Finally, we acknowledge the inherent challenges of working on this project that arise from the…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reis and Mensinger have reported that biographical information of diverse scientists should connect to the taught content rather than act as stand-alone elements, 4 whilst Gee et al suggest the use of "Try this" problems to connect with lecture material. 30 A study of student views on decolonization suggests that who is teaching the curriculum, and how it is delivered (e.g., through the use of active learning) are also important considerations. 37 Finally, we acknowledge the inherent challenges of working on this project that arise from the…”
Section: Discussionmentioning
confidence: 99%
“…We note that there have been a small number of other very recent publications reporting activities to introduce aspects of Diversity, Equity and Inclusion (DEI) into chemistry teaching that overlap to some extent with the work we present here. 4,25,29,30,31 For example, Gee et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reis and Mensinger report that biographical information of diverse scientists should connect to the taught content rather than act as stand-alone elements, 3 whilst Gee et al suggest the use of "Try this" problems to connect with lecture material. 30 A study of student views on decolonization suggests that who is teaching the curriculum, and how it is delivered (e.g. through the use of active learning) are also important considerations.…”
Section: Discussionmentioning
confidence: 99%
“…For example a student conference activity employing active learning, 29 foundational and extracurricular DEI activities, the creation of alumni profiles, 24 and the development of a "Not all Chemists are white men poster" and slide-show resource. 30 Pence and Pence have collated a number of sources of biographical information and present a "Profiles in Chemistry" virtual activity involving eight videos of women scientists and people of color. 31 Ries and Mensinger have created a "Diversity in Chemistry" web-based resource to support the inclusion of more diverse Chemists for example at the start of a lecture.…”
Section: Introductionmentioning
confidence: 99%